The seven faces of SIRT7 - Blank, Maximilian Felix; Grummt, Ingrid (Transcription, 2017)
SIRT7, a member of the sirtuin family of NAD+-dependent protein deacetylases, is a key mediator of many cellular activities. SIRT7 expression is linked to cell proliferation and oncogenic activity, connecting SIRT7-dependent regulation of ribosome biogenesis with checkpoints controlling cell cycle progression, metabolic homeostasis, stress resistance, aging and tumorigenesis. Despite this important functional link, the enzymatic activity, the molecular targets and physiological functions of SIRT7 are poorly defined. Here, we review recent progress in SIRT7 research and elaborate the main pathways in which SIRT7 participates.